Kebutuhan Perangkat Hukum Nasional dan Internasional dalam Rangka Penataan Dirgantara Nasional - Abdurrasyid, Priyatna (Indonesian Journal of International Law, 2006)
The need of space strategy, whether in land, in territorial water, in air or outer space, oftentimes oppose against commercial and academic need. In the other hand, also happened opposition among the need of sovereignty of international regime and territorial, which want the existence of an international rule, which specify delimitation between National and International space. The need of strategy National and sovereignty is a maximum height of national air. On the contrary, the need of international society is a rule of law which limit the minimum of the National Air Space broadness. In the end, sovereignty demand to Space prohibited by Article II Space Treaty 1967. However, state have jurisdiction to ship, airplane, installations, spaceship, which beyond its region, in international region, when the appliances have mentioned state nationality (based on Lotus Case 1926).